MENTORING AND PIONEERING MSMES IN THE FARMER GROUP (MEKAR JAYA) IN THE FORM OFAN TARO BENENG LEAF PROCESSOR AS AN ALTERNATIVE TO TOBACCO LEAVES FOR RAW MATERIALS OF HERBAL CIGARETTE PRODUCTS IN PALANYAR PANDEGLANG VILLAGE BANTEN - Rakhim Setya Permana, Basuki; Sumarna, Maman; Hermanto, Dadang; Meilani, Putri; Anggraini, Seftian; Lesmana, Tedi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2024)
Some residents of Palanyar Village are farmers and taro leaf businesses, but the management is still simple and not managed systematically and well planned, so it has not been able to provide maximum results. This assistance aims to increase competitiveness from small and medium-sized industrial businesses to independent small industries based on creative industries to increase product added value and attract the market. Methods of implementation through discussion, practice, mentoring, monitoring and evaluation. The results of this assistance show that not all tiny and medium tobacco industry businesses in Palanyar Village, which have not taken care of circular licenses, halal certificates, produce product innovation and online marketing, due to limited funds and human resources.